Digital Corporate Communication Strategy - Vaneshia Auryen; Adelina Adyaloka Rizky Aulia; Sofiatus Sak Kiyah; Amelia Putri; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
This systematic literature review explores digital corporate communication strategies in the context of the Industrial Revolution 4.0, focusing on two main issues: the influence of technology on enhancing non-technical competencies, specifically interdisciplinary collaboration, as well as managerial challenges and strategies for ensuring accountability, transparency, and compliance, especially in developing countries. The review reveals that integrating technologies such as AI, cloud computing, and e-learning, primarily through project-based learning approaches, is effective in closing skill gaps and building sustainable competitive advantage. However, this success faces complex challenges in developing countries, such as limited digital infrastructure, pedagogical literacy gaps, and risks related to cybersecurity and AI ethics. Therefore, the study concludes that holistic managerial strategies are required, including infrastructure investment, continuous training, clear policy development, and the implementation of robust digital governance. Organizational sustainability depends on an optimal balance between technological innovation, human competency enhancement, and a robust governance framework.